From Maryam to Musawah: The Evolution of Muslim Feminist Thought in Advocating Family Rights and Equality in Islamic Law - Nur Munirah; Norhayatun Norhayatun; Abdillah Muhamad Hasan; Wan Hosein Mahfodz (Arba: Jurnal Studi Keislaman, 2026)
The study of Muslim feminism emerged as a response to gender injustice in Islamic family law practices that still place women in a subordinate position, necessitating Islamic-based reforms aligned with contemporary principles of justice. The research gap lies in the lack of historical-transformative studies that systematically trace the shift in thought from early critiques of modernity to the formation of global advocacy networks that influence transnational family law policies. This study aims to identify the phases of Muslim feminist thought’s evolution, analyze hermeneutical shifts in the interpretation of religious texts, and evaluate the contributions of organizations such as Sisters in Islam and Musawah to the integration of equality values into family law reform. Using a qualitative method grounded in a critical literature review, this study examines the primary works of Muslim feminist figures, institutional advocacy documents, and academic literature from 1970 to 2025, employing thematic coding to identify patterns of thought transformation and advocacy strategies. The results of the study show three main findings: first, the initial critical phase that emphasized religious identity and resistance to Western modernity; second, the phase of constructing Islamic feminist theology through contextual reinterpretation of gender verses that prioritize egalitarian principles, human rights, and maqāṣid al-Sharīʻah; third, the phase of institutionalization of the movement characterized by the formation of advocacy networks, strategic litigation, increased family law literacy, and involvement in national and transnational policy recommendations. The conclusion confirms that the evolution of Muslim feminism has successfully bridged the gap between the theory and practice of legal reform, yielding increasingly tangible impacts. However, it still faces variations in acceptance across different country contexts and limitations in access to grassroots advocacy.